The determinants of working capital management in Indonesia and the Philippines - Cynthia Kartika Tjandra; Werner R. Murhadi; Arif Herlambang (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Purpose: This study aims to analyze and identify determinants of working capital of manufacturing firms listed on Indonesia and the Philippines Stock Exchanges. This study focuses on working capital because firms with inadequate working capital may experience operational difficulties and lead to financial distress. Thereby, firms must have adequate working capital.Design/Methodology/Approach: The study employed panel data, with the final sample for Indonesia was 630 years of observation, while for the Philippines, the sample used was 210 years of observation. The sample of the study was manufacturing firms listed on Indonesia and the Philippines Stock Exchanges.Findings: The study results in the Indonesian sample show that profitability and growth opportunities have a significant positive effect on working capital. Asset tangibility, firm age, and leverage have a significant negative effect on working capital. While operating cash flow and firm size have no effect on working capital. In comparison, the results in the Philippines sample show that profitability has a significant positive effect on working capital. Asset tangibility and leverage have a significant negative effect on working capital. While operating cash flow, growth opportunities, age, and firm size have no effect on working capital.Research Limitations: This study has limitations, namely observations done only on manufacturing firms listed on Indonesia and the Philippines Stock Exchanges. Further research can use a sample with broader coverage in the service sector and expand variables that might affect working capital requirements, especially in the Covid-19 pandemic.Practical Implications: For a firm’s decision-makers, this present study can be used as a reference in making decisions related to working capital management. Bad decision-making in determining the amount of working capital may lead to high capital costs and financial distress.Originality/Value: What factors affect the amount of working capital is an attractive topic for many researchers today. Poor working capital management will result in a firm not being able to meet its maturing obligations and may lead to financial distress. The use of samples in developing countries, namely Indonesia and the Philippines, that is relatively similar, making this present study unique. By using samples in developing countries, this study can investigate differences in results between developing countries.